2008
DOI: 10.1080/03009740701640209
|View full text |Cite
|
Sign up to set email alerts
|

Functional and morphological evaluation of hand microcirculation with nailfold capillaroscopy and laser Doppler imaging in Raynaud's and Sjögren's syndrome and poly/dermatomyositis

Abstract: By using nailfold capillaroscopy, abnormalities in capillary morphology can be detected, and by using LDI, the reduced blood flow in the capillaries can be detected. These investigations can be useful in the detection of SRS, or in distinguishing whether the reduced blood flow is due to primary/systemic autoimmune diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 26 publications
2
12
0
2
Order By: Relevance
“…The authors suggested that laser Doppler flowmetry may identify patients with secondary RP when NC images appeared normal. Szabo et al (27) compared NC and LDI at the nondominant ring finger in healthy controls and in patients with Sjögren's syndrome, polymyositis/dermatomyositis, and primary RP. They found decreased perfusion as compared with controls in all of the patient groups and found morphologic changes in patients with Sjögren's syndrome and polymyositis/dermatomyositis.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that laser Doppler flowmetry may identify patients with secondary RP when NC images appeared normal. Szabo et al (27) compared NC and LDI at the nondominant ring finger in healthy controls and in patients with Sjögren's syndrome, polymyositis/dermatomyositis, and primary RP. They found decreased perfusion as compared with controls in all of the patient groups and found morphologic changes in patients with Sjögren's syndrome and polymyositis/dermatomyositis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that LDPI is able to detect changes in SSc microvasculature, particularly when combined with NVC and thermal infrared imaging 13,32,33 . In addition, LDPI has been employed in a small group of patients to evaluate skin blood flow in secondary RP, hand-arm vibration syndrome, and morphea plaques [15][16][17] . Our study shows for the first time, in a representative group of patients, that LDPI is a useful noninvasive diagnostic technique for evaluating skin blood flow in patients with PRP and SSc.…”
Section: Discussionmentioning
confidence: 99%
“…LDPI can be useful for the detection of secondary RP, distinguishing whether the reduced blood flow is due to systemic autoimmune diseases, assessing peripheral vascular impairment in hand-arm vibration syndrome, and evaluating microvascular perfusion of morphea plaques [15][16][17] .…”
mentioning
confidence: 99%
“…Nailfold capillaroscopy was performed on the 2nd and 4th digit of both hands as a representation of capillary vasculature, with clinical restraints (including discomfort) limiting a fuller examination in this paediatric population [14,15]. The 4th finger of the non-dominant hand is thought to be the most representative of morphological features [16].…”
Section: Methodsmentioning
confidence: 99%